2016
DOI: 10.1016/j.ijgo.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening accountability for improved maternal and newborn health: A mapping of studies in Sub‐Saharan Africa

Abstract: There are few accountability mechanisms in MNH in Sub-Saharan Africa between decision-makers and those affected by those decisions with both the power and the will to enforce answerability. Increasing accountability depends not only on how mechanisms are enforced but also, on how providers and managers understand accountability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 55 publications
3
67
1
1
Order By: Relevance
“…Both facilities reportedly made use of perinatal meetings to discuss adverse cases, monitor and account for poor outcomes, but there was limited use of lessons learnt in Tinyade as compared to Chisomo, and the latter monitored implementation through meeting records. A recent literature review illustrated how accountability mechanisms, such as perinatal and maternal death surveillance reviews, have failed to make health care providers and managers account for the quality of services as implementation rates of recommendations from reviews were low ( Hilber et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both facilities reportedly made use of perinatal meetings to discuss adverse cases, monitor and account for poor outcomes, but there was limited use of lessons learnt in Tinyade as compared to Chisomo, and the latter monitored implementation through meeting records. A recent literature review illustrated how accountability mechanisms, such as perinatal and maternal death surveillance reviews, have failed to make health care providers and managers account for the quality of services as implementation rates of recommendations from reviews were low ( Hilber et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A good accountability mechanism fosters an environment of learning and improvement (as opposed to an environment of blaming and shaming) [34], and this is the central philosophy of the ICM MEAP.…”
Section: Discussionmentioning
confidence: 99%
“…A strong accountability mechanism includes a recourse mechanism, i.e. a process that can be triggered if the entity being held to account does not take the necessary remedial action identified during the monitoring and review phases [34]. In the case of the ICM MEAP, this recourse mechanism is the withholding of accreditation or reaccreditation.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have investigated the implementation of M/PDSR in selected countries, and some reviews have explored implementation factors for maternal death reviews or perinatal death audits, separately. For example, a structured literature review of accountability mechanisms for maternal and newborn health in sub-Saharan Africa found MDSR the most common mechanism for performance accountability 17. A systematic review of facility-based perinatal mortality audit in LMIC in 2009 identified 10 low-quality evaluations with mortality outcome data 10.…”
Section: Introductionmentioning
confidence: 99%
“…While there are valuable contributions to the literature, these previous reviews did not consider implementation theory to assess implementation of M/PDSR nor of the full range of types of maternal and/or perinatal death reviews 9 17 18. Implementation theory allows for more complex interventions to be unpacked and examined 19–24.…”
Section: Introductionmentioning
confidence: 99%